Pengembangan Wisata Kesehatan di Indonesia - Sandra Maleachi; Suwinto Johan; Angelina L.M. Chuadrey (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the development of health tourism in Indonesia through a comparison with Penang, Malaysia, as one of the main medical tourism destinations for Indonesian patients. The research employed a descriptive qualitative approach through in-depth interviews with three Indonesian patients who had received medical treatment in both Indonesia and Penang, along with accompanying family members. Secondary data were collected from academic journals, government reports, media publications, and regulations related to healthcare and tourism sectors. The findings indicate that Indonesian patients prefer medical treatment in Penang due to better healthcare service quality, professionalism of medical personnel, efficient hospital systems, competitive medical costs, and the ability of healthcare staff to communicate in the Indonesian language. Accessibility, service convenience, and Penang’s positive image as a trusted medical tourism destination also influence patient decisions. The study highlights that the development of health tourism in Indonesia requires strong government support, improvement of hospital quality, strengthening of healthcare human resources, and integration between healthcare and tourism sectors to enhance national competitiveness.